Development of high flux dynamic membrane based on hydrodynamic and mass transfer for enhanced antifouling property and dye removal. Issue 5 (October 2021) - Nyobe, Dieudonne; Bin, Liying; Fu, Lingfang; Li, Ping; Huang, Shaosong; Fu, Fenglian; Guan, Guoqing; Hao, Xiaogang; Tang, Bing
Abstract: For better understanding the antifouling property and dye removal efficiency dynamic membrane (DM), the effects of hydrodynamic and mass transfer were investigated. A DM filter developed by pre-depositing powdered activated carbon (PAC) on membranes support materials (MSM), at a permeate flux increasing to a critical flux region 275 ± 10 LMH, was exploited to characterize the DM formation mechanism, then illustrate its stability and applicability in performing dye wastewater treatment for reuse. Mass transport by permeate drag was found to be the mechanism by which momentum distribution extended the compaction of the dynamic layer which, when the thickness was adjusted, could control turbulent flow while minimizing friction loss then resulted in the improved permeate flux (237–254 LMH) and dye removal efficiency (≥ 99%). The obtained results especially demonstrated significant antifouling performance, as the highest flux decline ratio was 2.45%, and mass transfer decreased by 48% under a flow range velocity of 1.22–1.30 mm/s. These results also indicated that an increase in boundary layer thickness, which generated maximum shear stress, decreased the mass transfer resistance because it provided greater driving forces. The amplified shear stress appeared to be a way to normalize permeate flux with respect to internal hydrodynamic and improvement of hydrophobicity by increasing DM surface roughness (super-hydrophobic state β = 176°) on MSM. Therefore, the concept of DM proposed herein, and which lifetime could be predicted, application in textile wastewater treatment could provide water reuse far beyond the current demand. Graphical Abstract: ga1 Highlights: Dynamic Membrane (DM) with enhanced antifouling property for dye wastewater treatment was developed. DM formation flux is a critical flux resulting from mass transfer balance achievement. Strong shear stress at DM surface was effective in mitigating fouling while improving flux. Internal hydrodynamic and mass transfer were essential in increasing pollutants removal. The improved membranes materials surface roughness reached super-hydrophobic state β = 176°.